PENGGUNAAN MOBILE PHONE REMINDE RSEBAGAI UPAYA PENINGKATAN KEPATUHAN PENGOBATAN ARV PADA ORANG DENGAN HIV/AIDS (ODHA):A SYSTEMATIC REVIEW - Wenny Nugrahati Carsita; Alvian Pristy Windiramadhan (JURNAL KESEHATAN INDRA HUSADA, 2020)
Background: HIV/AIDS are currently a health problem that threatens Indonesia and many countries around the world. Adherence with taking medication is one of the important factors in the success of ART. The latest innovations in the use of Mobile Phone Reminder (MPR) such as messaging, telephone calls, and application use are considered successful in increasing medication compliance among patients undergoing ART and have been examined and implemented in many countries with high-quality evidence that shows success for patients in improving adherence . Objective: To find out the use of MPR in an effort to improve adherence in PLWHA. Method: This study uses a systematic review based on the Preferred Reporting Items for Systematic Reviews & Meta-Analyzes (PRISMA) to identify all literature published by using relevant keywords. Results: In the 10 articles we have analyzed, the use of mobile phone reminders has been used in several countries such as China, Malaysia, Kenya, India, Cameroon, Boston, Sandiego. The ways that can be done to use MPR by using the method of voice calls and text messages as a reminder and support for PLWHA to obediently ART. Conclusion: MPR can be used as an option in an effort to improve adherence in PLWHA